The main contradictions of ideology of liberalism - N. U. Matveeva (Ассоциация независимых экспертов «Центр изучения кризисного общества» (in English: Association for independent experts “Center for Crisis Society Studies”), 2015)
The author raises the question about the causes of the crisis state of European culture. The article considers the ideological aspects of liberalism as the semantic foundations of the European culture. The article identifies the internal problems of the liberal ideology. The author draws the conclusion about the need for a new understanding of liberal values based on Christian roots of European culture.